The effects of bio priming on some of germination index of Faridan accession of Pimpinella anisum L. under drought stress - atfeh hoseini; امین صالحی; َAli Moradi; H.R. Balouchi (علوم و فناوری بذر ایران, 2020)
In order to investigate seed bio-priming effects on some germination index of Pimpinella anisum L. under drought stress, this research was done in genetic lab at Agriculture department of Yasouj University. The experiment was factorial with two factor based on CRD design in 4 replications and in each Petri dishe 30 seeds were planted. First factor was seed bio-priming with nine level (on bio-priming, 4 Bactria strain (P.fluorescent), fluorescent (CHA0), 1) P.F (, 2) P.F (, 16) B (and 52 (B)) and 4 strain of T.harzianum (T29, T32, T43, T36 and T39) and second factor include osmotic potential of drought stress in 3 levels (0, -3 and -6 bar). The evaluated traits in this study included germination percentage, germination rate, seedling length, dry weight, seedling vigour index (weight and length) and alometric coefficient. Results of test showed that increasing drought stress, decreased seed germination indexes, and bio-priming couldn’t improve these indexes than non-priming seeds, therefore in each of drought stress potential, T36 has the maximum germination percentage (83.88), germination rate (4.7), seedling length vigor index (10), seedling dry weight (8.07), and seedling weight vigor index (15.25) and not primed seeds have the lowest amount of this traits. According to the results, it can be stated that the application of bio-priming treatment can moderately reduce the adverse effects of drought stress in the germination stage of pimpinella anisum L.